PENINGKATAN HASIL BELAJAR IPS MATERI BENUA MELALUI MODEL QUIZ TEAM DIPADU MEDIA PETAKUMPET PADA SISWA KELAS VI SDN SIDOKARE 3 SIDOARJO - Sunarsih Sunarsih (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2017)
The problem in social studies in the 4th students of Sidokare 3 Elementary School shows that students learning outcomes on the continent material have not yet reached the KKM. The incomplete achievement of student learning outcomes is caused that most of students do not understand abaut the names and locations of coutries and have not been able to mention the characteristics of large countries on each continent. That is caused by the teachers are still oriented by textbooks, the lessons are still focus on memorization, the methods applied by teachers tend to be teacher activities not students activities and also less use of leaning media. An alternative solution to the problem is using the Team Quiz model combined with Petak Umpet Media. This study used CAR model. The research subject were 4th Sidokare 3 students of 35. The result showed that in the pre-cycle of 46%, the first cycle was 71%, and the second cycle was 94%. The conclusion is that the Team Quiz model combined with Petak Umpet Media can improve the learning outcomes of continental social studies material in 4th Sidokare Elementary School students of Sidoarjo.